Bullous Systemic Lupus Erythematosus: case report - Miziara,Ivan Dieb (2013)
INTRODUCTION: Bullous systemic lupus erythematosus (BSLE) is an autoantibody-mediated disease with subepidermal blisters. It is a rare form of presentation of SLE that occurs in less than 5% of cases of lupus. CASE REPORT: A 27-year-old, female, FRS patient reported the appearance of painful bullous lesions in the left nasal wing and left buccal mucosa that displayed sudden and rapid growth. She sought advice from emergency dermatology staff 15 days after onset and was hospitalized with suspected bullous disease. Intravenous antibiotics and steroids were administered initially, but the patient showed no improvement during hospitalization. She displayed further extensive injuries to the trunk, axillae, and vulva as well as disruption of the bullous lesions, which remained as hyperemic scars. Incisional biopsy of a lesion in the left buccal mucosa was performed, and pathological results indicated mucositis with extensive erosion and the presence of a predominantly neutrophilic infiltrate with degeneration of basal cells and apoptotic keratinocytes. Under direct immunofluorescence, the skin showed anti-IgA, anti-IgM, and anti-IgG linear fluorescence on the continuous dermal side of the cleavage. Indirect immunofluorescence of the skin showed conjugated anti-IgA, was anti-IgM negative, and displayed pemphigus in conjunction with anti-IgG fluorescence in the nucleus of keratinocytes, consistent with a diagnosis of bullous lupus erythematosus. DISCUSSION: BSLE is an acquired autoimmune bullous disease caused by autoantibodies against type VII collagen or other components of the junctional zone, epidermis, and dermis. It must be differentiated from the secondary bubbles and vacuolar degeneration of the basement membrane that may occur in acute and subacute cutaneous lupus erythematosus.